From Influence to Impact: Supporting Quality Improvement in Independent Primary Care Practices - Nancy Maulick; John Stoeckle; Wayne Stephens; Cathryn Kelly; Pamela Fisher; Jennifer Stephens (Population Health Management, 2026)
Clinically integrated networks (CINs) and physician-hospital organizations (PHOs) participating in value-based care (VBC) are accountable for quality across both employed and independent practices. Employed practices benefit from shared electronic health records (EHRs), standardized workflows, and centralized oversight. Independent practices present distinct challenges, including EHR heterogeneity, variable billing workflows, limited administrative infrastructure, and lack of direct operational control. Despite representing a substantial proportion of attributed lives, structured approaches to quality improvement (QI) in these settings remain limited. The authors designed and implemented a structured, practice-level QI intervention for independent primary care practices within a large PHO. The model was evaluated using the RE-AIM framework, with the Consolidated Framework for Implementation Research (CFIR) applied to characterize implementation. Core components included individualized practice assessment, a staged workflow approach (retrospective catch-up, real-time visit optimization, and clinician engagement), personalized performance feedback, and relationship-based support adaptable across heterogeneous EHR environments. Twenty-two practices were included; 15 engaged in the intervention over 21 months (March 2024–November 2025). Engaged practices improved mean composite quality scores from 42.9% (SD: 24.1) to 51.8% (SD: 28.6; +9.0 points; P = 0.005). Nonengaged practices declined from 23.3% (SD: 18.3) to 18.0% (SD: 11.2; −5.4 points; P = 0.65). The between-group effect size was large (Cohen’s d = 0.85). Improvements occurred across all nonintegrated EHR systems. A relationship-centered, staged, and tailored approach can improve quality performance in independent practices despite structural constraints. This model provides a scalable framework for integrated delivery networks to drive performance across both employed and independent settings.